Identification and characterization of a SARS-CoV-2 specific CD8+ T cell response with immunodominant features - Gangaev, Anastasia; Ketelaars, Steven L. C.; Isaeva, Olga I.; Patiwael, Sanne; Dopler, Anna; Hoefakker, Kelly; De Biasi, Sara; Gibellini, Lara; Mussini, Cristina; Guaraldi, Giovanni; Girardis, Massimo; Ormeno, Cami M. P. Talavera; et al. (Nature communications, 2021)
The COVID-19 pandemic caused by SARS-CoV-2 is a continuous challenge worldwide, and there is an urgent need to map the landscape of immunogenic and immunodominant epitopes recognized by CD8 + T cells. Here, we analyze samples from 31 patients with COVID-19 for CD8 + T cell recognition of 500 peptide-HLA class I complexes, restricted by 10 common HLA alleles. We identify 18 CD8 + T cell recognized SARS-CoV-2 epitopes, including an epitope with immunodominant features derived from ORF1ab and restricted by HLA-A*01:01. In-depth characterization of SARS-CoV-2-specific CD8 + T cell responses of patients with acute critical and severe disease reveals high expression of NKG2A, lack of cytokine production and a gene expression profile inhibiting T cell re-activation and migration while sustaining survival. SARS-CoV-2-specific CD8 + T cell responses are detectable up to 5 months after recovery from critical and severe disease, and these responses convert from dysfunctional effector to functional memory CD8 + T cells during convalescence. Many viral antigens have been identified in patients with COVID-19 patients, but which of these result in meaningful immune responses is unclear. Here the authors identify a range of SARS-CoV-2 CD8 + T cell responses across patients including a response targeting an epitope of ORF1ab with immunodominant properties.